PENGARUH KEADILAN PAJAK, TARIF PAJAK, DISKRIMINASI PERPAJAKAN DAN TEKNOLOGI INFORMASI TERHADAP PERSEPSI WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK (TAX EVASION) (Studi Empiris pada KPP Pratama Senapelan Pekanbaru 2015-2016) - Anton, Afri; Agusti, Restu; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine and analyze the effect of tax fairness, tax rates, tax discrimination and information technology to taxpayer’s perception of tax evasion (tax evasion). The sample in this study is an individual taxpayer conducting business with a turnover under 4.8 billion per year and listed on KPP Pratama Senapelan Pekanbaru. The sampling technique used purposive sampling method and the determination of the number of samples in this study are calculated through a formula slovin obtained by 100 respondents. Data of this study uses primary data directly through questionnaire and analyzed using SPSS for Windows version 20. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. Results of research conducted showed tax fairness has effect on the perception of tax evasion , the tax rate has no effect, tax discrimination has no effect, and information technology has no effect on the perception of tax evasion (tax evasion) in sig. t <0.05.Keywords: Tax Fairness, Tax Rates, Tax Discrimination, Information Technology, Perception Tax Evasion.